2018
DOI: 10.1186/s12889-018-6096-z
|View full text |Cite
|
Sign up to set email alerts
|

Raising cigarette excise tax to reduce consumption in low-and middle-income countries of the Asia-Pacific region:a simulation of the anticipated health and taxation revenues impacts

Abstract: Background According to the World Health Organization (WHO), 80% of the world’s smokers live in low- and middle-income countries. Moreover, more than half of the world’s smoking-addicted population resides in the Asia-Pacific region. The reduction of tobacco consumption has thus become one of the major social policies in the region. This study investigates the effects of price increases on cigarette consumption, tobacco tax revenues and reduction in smoking-caused mortality in 22 low-income as well as middle-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
2
45
0
Order By: Relevance
“…Additionally, the number of averted smoking-attributable deaths (SADs) would be highest in China, followed by Indonesia and India. In total, the simulation study found that there would be over 17.96 million lives saved by an increase in cigarette taxes [19].…”
Section: Support Towards Stronger Tobacco Controlmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, the number of averted smoking-attributable deaths (SADs) would be highest in China, followed by Indonesia and India. In total, the simulation study found that there would be over 17.96 million lives saved by an increase in cigarette taxes [19].…”
Section: Support Towards Stronger Tobacco Controlmentioning
confidence: 98%
“…The excise tax increase is known to have a significant effect on the reduction of smoking prevalence and the number of smoking-attributable deaths. A simulation study in low-and middle-income countries in the Asia-Pacific Region was conducted and showed that, given an average annual cigarette price increase of 9.5%, the average annual cigarette consumption would decrease by 3.6% [19]. On the other hand, the average annual tobacco tax revenue would increase by 16.2%.…”
Section: Support Towards Stronger Tobacco Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Risky Kusuma Hartono 1,2 *, Sabariah Abd Hamid 2 , Muhammad Hafizurrachman 1 According to the World Health Organization (WHO), 80% of the world's smokers live in low and middleincome countries and more than half of the world's smoking-addicted population resides in the Asia-Pacific region (WHO, 2015;Ho et al, 2018). In Indonesia, cancer due to smoke causes 74.440 people death with the dominant cases happens in man (95%) (Riskesdas, 2013;Kristina et al, 2015;Tandilittin, 2016).…”
Section: Do the Number Of Cigarettes Smokes Per Day Contribute To Thementioning
confidence: 99%
“…Cigarettes have generally become less affordable in developed economies over time, with increased taxes and small increases in income, but more affordable in developing countries, where there have been minimal changes in taxes (Chaloupka et al 2019). Studies by the WHO suggest that 80 per cent of the world's smokers live in low-and middle-income countries (LMICs), and more than 80 per cent of those dying from tobacco-related diseases will be from those countries by 2030 (Ho et. al.…”
Section: Introductionmentioning
confidence: 99%